Strategy for Innovation and Knowledge Creation in the Aeronautical Industrial Cluster in Campania Region - Riccardo Cappellin; Eugenio Corti; Massimiliano Bianca (European Regional Science Association (ERSA), 2006)
This empirical study is a part of a large theoretical and empirical research project, "IKINET – International Knowledge and Innovation Network" (EU FP6, N° CIT2-CT-2004-506242), coordinated by University of Roma "Tor Vergata", on the international/interregional dimension of existing knowledge and innovation networks, where not only information or codified knowledge, as in the collaboration between RTD institutions, but also tacit knowledge, know-how and competencies circulate. With particular focus on how to decrease the "organisational and institutional distance" between the various regions at the international/interregional level, since tacit knowledge and innovation capabilities often are embodied in human capital and individual organisations and institutions. The aim of the paper is to identify the key barriers to an efficient operation of knowledge creation and transfer and innovation networks in the Aeronautical Industrial Cluster in Campania Region, in the south of Italy. In Campania there is a long tradition in this sector and today there are about sixty enterprise that work in the sector, we use, like sample of the regional industrial, fifteen enterprise subdivide in large primer contractor and suppliers of first and second range. Information and data on the selected sample are colleted, and also by suitable questionnaires, and interviews, that the authors have submitted to the entrepreneurs and to the top managers of either the enterprises. We focalize our analysis on firm recent performance and related factor of competitiveness; organizational characteristics of the firms, competencies and management of human resources; innovation history and knowledge creation and transfer processes within the firms; finally we analyze from qualitative point of view relevance of enterprise in the cluster like technological crux. Examined sample give back a realty extremely composed with strategy really different but with some common aim and operative behaviourism that let us to deduce some homogenous group.
Keywords: 330